SANITASI RUMAH IBADAH (MASJID) DAN PERILAKU MARBOT MASJID DI KOTA TANJUNGPINANG - Putri, Annisa Pratiwi (STIKES ADVAITA MEDIKA TABANAN, 2024)
It is commonly found that the mosque’s sanitation problems still do not health requirements, for instance, prayer mats are not properly maintained, limited water supply, slippery mossy floor, the absence of water closet, inadequate ventilation and lighting system. The conducted preliminary survey showed that the sanitation condition of the mosque stayed under minimum standard such as scattered garbage in the ditch, inadequate quantity of covered bin, yellowish spots on the ceiling surface, etc. The purpose of this study is to portray the sanitation system of the observed mosques and the behavior of the mosques’ Marbots in Tanjungpinang City. This research is a descriptive survey by conducting observations and interviews, in accordance with Keputusan Menteri Kesehatan Number 288 Year 2003, with 184 of the number of the population, and the number of samples is 65 that were chosen using stratified random sampling technique. The results show that there were 65 (100%) mosques that met the requirement of the condition of the environment and the mosque’s utility, the sanitation system standard was fulfilled by 54 mosques (83,1%), and there were 5 marbots (7,7%) who had good behavior. Hence, it is necessary that the marbots of the mosques might improve their behavior related to the mosques’ sanitation.